PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PERUSAHAAN JASA - Ratna Sari (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2022)
This study aims to determine the effect of financial performance on the share price of service companies listed on the Indonesia Stock Exchange. The data collection technique is carried out by the documentation method. Go through the questionnaire distributed. The number of samples in this study was 12 companies. Data analysis was performed by multiple linear regression analysis. The results showed that: 1) Current Ratio (CR) performance has a positive and significant effect on the price of the company concerned. 2) The performance of the Debt to Equity Ratio (DER) has a positive and significant effect on the price of the company concerned. The data used in this study is quantitative data. Quantitative data is data in the form of numbers, the value can change or vary. Data collection techniques are carried out by documentation methods, namely from existing documents or stored records, be it in the form of transcript notes, books, newspapers, and so on. The data is accessed via the internet on the IDX website, namely www.idx.co.id. The data consists of Current Ratio (CR), Debts to Equity Ratio (DER) data. The results of the study found that the Current Ratio has a significant effect on the stock price of service companies in the transportation sector listed on the IDX in 2015-2018. Debt to Equity Ratio has a significant effect on the share price of service companies in the transportation sector listed on the IDX in 2015-2018. From the results of the anova test or F-test, obtained F-count = 12,691 and a signification value of 0.000, smaller than 0.05, meaning that the variable current ratio and debt equity ratio simultaneously have a positive and significant effect on stock prices (close).